Evaluation of cost effective adsorbent and biochar from Malaysia oil palm wastes: synthesis, characterisation and optimisation studies - Xin Jiat, Lee (2018)
The rapid development of palm oil industry in Malaysia has generated significant amount of solid and liquid wastes, contributing to major environmental issues in the past five decades. Palm oil residues such as palm kernel shell (PKS), empty fruit bunch (EFB) and palm oil sludge (POS) are difficult to be disposed of. Thus, the potential application of the oil palm wastes for synthesis of value added products such as adsorbents for heavy metals removal and solid biochars for fuel generation, are presented in this thesis.